Exploring potential pathways between parity and tooth loss among American women. - Russell, Stefanie L; Ickovics, Jeannette R; Yaffee, Robert A (American journal of public health, 2008)
We assessed the impact of parity on tooth loss among American women and examined mediators of this relationship.
Keywords: African Americans; Aged; Aged, 80 and over; European Continental Ancestry Group; Female; Health Behavior; Health Status; Humans; Life Style; Oral Health; Parity; Pregnancy; Regression Analysis; Risk Factors; Tooth Loss; United States; Women's Health